Around a Masterpiece. The Appearance of Messiah of Alexander Ivanov: Farts and Myths, “Secrets” and Scientific Problems - Stepanova, Svetlana S. (Actual Problems of Theory and History of Art, 2018)
After the publication by the author of the present paper the monograph on Alexander Ivanov in 2012 research work was focused on the attribution of the works of A. A. Ivanov, the search for the sources of his artistic method and developing a strategy for further comprehensive research. The report summarizes scientific museum research and clarifies certain important facts related to the heritage of Alexander Ivanov. One of the enduring myths is the presence among the characters of painting “The Appearance of Messiah” of Nikolai Gogol and of the artist himself in the form of the so-called “Closest to Christ” and “Traveler”. But a number of facts and written evidence of Ivanov speak against such interpretations that distort the essence of his creative method, as well as the nature of his relationship with the writer. Specific features of sketch material, the availability of large-scale author works, raise questions about some of the nuances of the artist’s painting method. Traditional extended dating of the painting (1837-1857) and the relevant sketches also need to be corrected, using both archive and technical and technological researches. In 2009 for the first time the collection of Ivanov’s works from Tretyakov State Gallery and the State Russian Museum appeared in the media project (CD-Rom “Alexander Ivanov. Paintings”). This allowed grouping the sketches thematically (by characters and typologies). This CD-Rom can become a basis for the encyclopedia about the artist.
Keywords: historical paintings; the Italian sources of creativity; drawings; sketches; attribution; the creative process; the creative method; N. Gogol